2013
DOI: 10.3109/08982104.2013.810644
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and characterization of nanoliposomal 5-fluorouracil for cancer nanotherapy

Abstract: A scalable and safe method was developed to prepare nanoliposome carriers for the entrapment and delivery of 5-fluorouracil (5-FU). The carrier systems were composed of endogenously occurring dipalmitoylphosphatidylcholine (DPPC), negatively charged dicetylphosphate (DCP), cholesterol (CHOL) and glycerol (3%, v/v). Nanoliposomes were prepared by the heating method in which no harmful chemical or procedure is involved. Results indicated fast and reproducible formation of non-toxic liposomes that possess high en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 48 publications
0
18
1
Order By: Relevance
“…Over the course of 3 months, the mean particle size of formulations did not change significantly ( P > 0.05). This matter could be resulted by the presence of transcutol in the formulation that may cause flexibility in vesicles [ 30 ] and cholesterol that has stabilizing effect against aggregation and fusion of the liposomes [ 37 ]. Similar results obtained by Mura et al [ 38 ] that found particle size of PEVs with different amounts of transcutol remained constant during 3 months at 4 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Over the course of 3 months, the mean particle size of formulations did not change significantly ( P > 0.05). This matter could be resulted by the presence of transcutol in the formulation that may cause flexibility in vesicles [ 30 ] and cholesterol that has stabilizing effect against aggregation and fusion of the liposomes [ 37 ]. Similar results obtained by Mura et al [ 38 ] that found particle size of PEVs with different amounts of transcutol remained constant during 3 months at 4 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Kaiser et al [41] argued that this effect depends on the lipid composition, the packing of the acyl chains, and particularly applies to water-soluble compounds in small liposomes, due to the small ratio between the inner and external volume. Also, Elmeshad et al [42], observed that there was a directly proportional relationship between the size of the vesicle, the subsequent aqueous space, and the amount of 5FU encapsulated. Fig.…”
Section: Physicochemical Characterization Of Udl-5fumentioning
confidence: 98%
“…However, there appeared to be no association between the mean particle sizes of AR liposomes and the AR to lipid ratios for each method of preparation. These results could be attributed to the water-solubility of AR, which would lead to it being predominantly entrapped in the aqueous compartment rather than in the lipid bilayer of liposomes (12).…”
Section: Resultsmentioning
confidence: 99%